Design and Development of EcoHike: A Mountain Climbing Game as an Environmental Education Medium Based on Roblox Studio - Nasution, Ari Akbar; Afif Badawi; Leni Marlina (Bahasa Indonesia, 2026)
Environmental degradation in Indonesia remains a serious issue due to the low level of public awareness in maintaining environmental cleanliness and sustainability. Conventional environmental education methods are considered less effective, especially for digital generations who require interactive and engaging learning media. Therefore, this study aims to design and develop EcoHike, an educational game with a mountain hiking theme based on Roblox Studio as a medium for environmental education. The EcoHike game is designed by integrating concepts of environmental cleanliness, nature conservation, and responsibility toward nature into interactive gameplay. The research method focuses on the game design and development stage using the Lua programming language, with limited testing on functionality and user experience aspects. The results of this study are expected to increase players’ awareness and understanding of the importance of environmental sustainability through a game-based learning approach, as well as demonstrate the potential of Roblox Studio as an innovative and accessible digital learning media platform.